'I hate to be the feminist here…': reading the post-epitaph chick flick. Issue 6 (2nd November 2017) - Cobb, Shelley; Negra, Diane
Abstract: Numerous accounts in recent years have announced (often zealously) the death of the chick flick, a genre whose output has conspicuously slowed since a peak in the 1990s. We analyse here two recent hits from the 'post-epitaph' phase in order to understand the kinds of generic updates such films are attempting and how they place women in regard to changing gender norms and the conditions of neoliberal capitalism. We find that in Trainwreck (2015) and The Intern (2015) female protagonists' affiliation with patriarchal power structures is re-confirmed and both films ultimately retain a commitment to a rigid order unwilling to countenance female sexual agency or envision more flexible economic arrangements.